Re-examination of the genus-level taxonomy of the pollen beetle subfamily Meligethinae – Part 1. Sagittogethes Audisio and Cline 2009 and allied genera; with description of a new genus (Coleoptera: Nitidulidae) - Meike Liu; Min Huang; Andrew Richard Cline; Paolo Cardoli; Paolo Audisio; Simone Sabatelli (Fragmenta entomologica, 2020)
Recent molecular and morphological data derived from members of the pollen-beetle subfamily Meligethinae suggest the need to separate the genus Sagittogethes Audisio and Cline, 2009, including species mostly distributed in Western Palaearctic areas, into two distinct (although related) genera, Sagittogethes and Teucriogethes gen. n. This new genus, comprising the Western European Meligethes obscurus Erichson, 1845 as its type species, includes less than ten species distributed between the Iberian Peninsula and North Africa westward, and China and Japan eastward. All inclusive species utilize members of the genus Teucrium L. (Lamiacaeae: Ajugoideae) as larval host-plants. Morphological and bionomical information, and molecular data clearly demonstrate the necessity for updating the taxonomic position of the two clades. Based on molecular evidence, the new genus represents the sister-group of Thymogethes Audisio and Cline, 2009, while the sister-group relationships of the remaining Sagittogethes taxa with other Lamiaceae-associated genera of Meligethinae remain uncertain. Within the new genus, the relictual and rare Western Mediterranean species T. minutus (C.N.F. Brisout de Barneville, 1863) seems to occupy an isolated position.